Audience 1 versus Audience 2: Adapting a project for multiple audiences using verbal and multimedia platforms. Issue 2 (3rd April 2021) - Seroka, Laura
Abstract : Students are challenged to write papers and give oral presentations across disciplines. Yet, the audience for students often remains the same: college personnel and classroom peers. Communication classrooms are ideal places to learn about and practice audience adaptation, specifically modifying content for different audiences, contexts, and platforms. This assignment allows students to develop an informative presentation for their classroom peers and then to adapt the content to a multimedia platform designed to benefit a specific community-based organization or audience. Courses: Introduction to Communication, Introduction to Business or Organizational Communication, Public Speaking. Objectives: By completing this activity, students should be able to: (1) identify, research, and understand target audiences; (2) evaluate critically and adapt information for new and emerging audiences; (3) craft and communicate effective messages in various presentational contexts and platforms; and (4) build and develop skills for working in teams, including collaboration and peer evaluation.